Analisis Efektivitas Program Insentif Pajak terhadap Daya Saing UMKM - Utari, Mardian; Salsabila, Laila Syakila; Maemunah, Maemunah (Lembaga Publikasi Ilmiah Nusantara, 2025)
Tax incentive programs are one of the fiscal policies implemented by the government to support the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to analyze the effectiveness of tax incentive programs in enhancing MSMEs’ competitiveness, particularly in terms of business sustainability, productivity improvement, and market expansion. The research method employed is a descriptive quantitative approach by collecting data through questionnaires and interviews with MSME actors registered in [region name]. Data analysis was conducted using simple linear regression to determine the influence of tax incentives on MSME competitiveness indicators. The results indicate that tax incentive programs have a positive and significant impact on increasing MSME competitiveness. Incentives such as reduced tax rates and deferred payments have been proven to provide wider financial space for MSMEs to increase production capacity, improve product quality, and expand marketing networks. However, the effectiveness of this program still faces challenges, such as the low level of MSME taxpayers’ understanding of tax regulations and limited access to information regarding tax incentives. In conclusion, tax incentive programs are effective in improving MSME competitiveness but must be accompanied by efforts to increase tax literacy and more intensive assistance from tax authorities. The recommendation of this study is the need for synergy between the government, tax consultants, and financial institutions to create a highly competitive MSME ecosystem in the globalization era.